SOCIO-ECONOMIC IMPLICATIONS OF A YOUNGER AGED FEMALE PREDILECTION IN MALIGNANT TRANSFORMATION OF ORAL SUB MUCOUS FIBROSIS - Fatima, Nazish; Mohiuddin, Sidra; Hosein, Salim; Hosein, Mervyn (Journal of Ayub Medical College Abbottabad, 2018)
Background: This study was conducted to determine the age, gender and pattern of associated chewing habits among cases of oral squamous cell carcinoma (OSCC) presenting with, (OSMFCa) and without, (Ca-OSMF) pre-existing clinical oral submucous fibrosis in Karachi, Pakistan. Method: A cross sectional, multi centric study of (n=1009) cases with histologically confirmed oral squamous cell carcinoma seen at both public, private tertiary care hospitals and clinics over a period of eight years. A non-probability convenience sampling was used for selection of cases. Of these n=472 cases were reported as malignant transformation of clinical OSMF into OSCC: (OSMFCa) and n=537 were of OSCC without clinical evidence of OSMF: (Ca-OSMF). Qualitative analysis for gender and chewing patterns as well as chi square was performed for association. Age comparison between the OSMFCa and Ca-OSMF groups were performed by independent t test. Results: A total of n=1009 cases presenting with OSCC were examined. Of these 46.78% (n=472) cases were reported as OSMFCa and 53.22% (n=537) as Ca-OSMF. The comparison of age differences at presentation of OSMFCa and Ca-OSMF cases by independent t test was statistically significant (p<0.049). Both gender and chewing habits showed significant association with OSMFCa and Ca-OSMF. Conclusion: Common to both affected groups was consumption of betel quid, chewing tobacco and variants with males tending to move on to more complex combinations. An overall male trend was noted in OSCC, particularly in Ca-OSMF. However, proportion of females with OSMFCa was significantly higher than males. A significantly younger female affectation in this group has significant potential socio-economic consequences. Keywords: Malignant transformation; Carcinogenesis; Oral submucous fibrosis; Oral squamous cell carcinoma; South Asia